2021
DOI: 10.18632/aging.202589
|View full text |Cite
|
Sign up to set email alerts
|

The aging-related risk signature in colorectal cancer

Abstract: Background: Colorectal cancer (CRC) is the third most common cancer worldwide. The opening of the TCGA and GEO databases has promoted the progress of CRC prognostic assessment, while the aging-related risk signature has never been mentioned. Methods: R software packages, GSEA software, Venn diagram, Metascape, STRING, Cytoscape, cBioPortal, TIMER and GeneMANIA website were used in this study. Results: Aging-related gene sets, GO_AGING, GO_CELL_AGING and GO_CELLULAR_SENESCENCE, were activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 42 publications
0
62
0
Order By: Relevance
“…10,17 Aging can also promote carcinogenesis, tumor development and metastasis, 13,14,[17][18][19] and is a significant risk factor for colorectal tumor and lung carcinoma. 20,21 Therefore, novel aging-related markers can potentially be used to predict cancer prognosis, 33 so it is vital to understand the association between signature of aging and BC. In this study, our nomogram presented good calibration and discrimination in the TCGA set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,17 Aging can also promote carcinogenesis, tumor development and metastasis, 13,14,[17][18][19] and is a significant risk factor for colorectal tumor and lung carcinoma. 20,21 Therefore, novel aging-related markers can potentially be used to predict cancer prognosis, 33 so it is vital to understand the association between signature of aging and BC. In this study, our nomogram presented good calibration and discrimination in the TCGA set.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,[17][18][19] Identifying key characteristics and induction of senescence in tumor cells has been a recent focus of cancer research, 13 as researchers have explored and confirmed their potential diagnostic or prognostic value as biomarkers in malignancy, including colorectal and lung cancer. 10,20,21 However, its prognostic value in BC remains unknown as no precise clinical signature has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed a model constructed using age-related genes to aid in the prediction of outcome in colorectal cancer patients. 21 In glioma, aging has been found to be the strongest risk factor for disease progression, and the survival of glioma patients can be predicted by analyzing brain aging. 22 However, markers for aging-related gene in predicting the survival rate of OC patients have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Based on TCGA and GEO, many risk models have been developed to predict the OS of CRC patients; most of these are mechanism-driven models based on factors such as aging, hypoxia, and autophagy [ 9 , 10 , 11 ]. However, a fibroblast-related risk signature based on open database has not been established to date.…”
Section: Discussionmentioning
confidence: 99%